Creating Running Text as a Digital Information Board Based on an Android Application Using the HD-WF2 Controller - Subekti, Eko Prasetyo; Eno, Muhammad; Iswahyudi (Cattleya Darmaya Fortuna, 2025)
Running text is a form of digital media that can display moving text and animations. Until now, many users still update and change text data manually using USB connections, flash drives, and computer keyboards. This means they must interact directly with the running text. This research aims to create a running text that utilizes wireless technology and Android phones using applications connected via a Wi-Fi network. By utilizing an Android application and a Wi-Fi-based HD-WF2 microcontroller as an operational control on the running text, the test results show that the created moving text can be an alternative solution to facilitate the delivery of information and can function at a distance of 20 meters without obstacles and 10 meters with obstacles.